Diversity Of Soil Macrofauna On Several Land Use On Peatlands - Wuri Handayani; Aji Winara (Jurnal Agroforestri Indonesia, 2020)
Peatlands are very vulnerable to land use change. Some of the current peatland cover conditions include agricultural cultivation lands, plantations, shrubs and secondary forest. The presence of soil macrofauna as a soil ecosystem engineer can be a bio-indicator of peatland fertility. This study aims to analyze the diversity of soil macrofauna in several patterns of peat land use in cultivated areas. The research was conducted in December 2017 in Rasau Jaya District, Kubu Raya Regency, West Kalimantan Province. The research method used is monolithic technique with descriptive data analysis using the alpha and beta diversity index approach. The results showed that the diversity and diversity of macrofauna species on peatlands were classified as medium and low, with the highest diversity found in secondary forest patterns (H '= 2.09) and the lowest in oil palm plantations (H' = 0.73), while species richness was found. The highest was found in secondary forest (R '= 4.01) and the lowest was in oil palm plantations (R' = 1.42). The highest population density and abundance were the order Isoptera and Opisthopora, while the lowest is Dermaptera. Several groups of macrofauna which are used as bioindicators of land fertility are found in all land use patterns with  the dominan order is Isoptera and Opisthopora. Soil temperature and acidity conditions affect soil macrofauna population density. The presence of diverse vegetation and adequate canopy can affect environmental conditions and the diversity of soil macrofauna. Based on the diversity of soil macrofauna, cultivation with an agroforestry pattern is preferable to peatlands.